Cross‐entropy‐based joint carrier frequency offset estimation and multiuser detection for multicarrier code division multiple access systems. (6th December 2011) - Lain, Jenn‐Kaie; Yang, Shang‐Yi; Lin, Chih‐Wei
SUMMARY: This paper presents a joint carrier frequency offset estimation and multiuser detection based on a maximum likelihood approach in multicarrier code division multiple access systems. With the definition of a score function based on the log‐likelihood, the joint carrier frequency offset estimation and multiuser detection can be formulated as a nonlinear optimization problem over the joint of a multidimensional real space and a multidimensional discrete space. To reduce the computational complexity required by the joint decision statistic, while still obtaining a desirable performance, a new method using cross‐entropy optimization is proposed to solve the nonlinear optimization problem. Because of the robustness of the cross‐entropy optimization, the joint decision statistic can be efficiently solved, and, as shown by the furnished simulation results, the proposed approach can achieve satisfactory performance in various scenarios. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : To reduce the computational complexity required by the joint carrier frequency offset estimation and multiuser detection, while still obtaining a desirable performance, a new method using cross‐entropy optimization is proposed to solve the nonlinear optimization problem. Because of the robustness of the cross‐entropy optimization, the joint decision statistic can be efficiently solved, and, as shown by the furnished simulation results, the proposed approach can achieve satisfactory performance in various scenarios.